Effect of Dhikr Therapy on Quality of Life in Hemodialysis Patients with Chronic Kidney Disease - Ayulia, Viqy; Hidayat, Rahmat (Bantayang Omni Cendekia, 2024)
Background: Patients with chronic kidney disease undergoing hemodialysis require continuous treatment to maintain life expectancy. Beyond physical care, these patients also need psychological, social, and spiritual support, which aligns with the principles of palliative care. Dhikr therapy, as a form of spiritual intervention, may improve patients' quality of life by reducing psychological distress and enhancing spiritual well-being. Objective: This study aimed to examine the effect of dhikr therapy on the quality of life of patients with chronic kidney disease undergoing hemodialysis at Labuang Baji Hospital, Makassar. Methods: This quasi-experimental study employed a pretest-posttest design without a control group. A total of 30 respondents were selected using purposive sampling. Quality of life was measured using the WHOQOL-BREF instrument. Dhikr therapy was provided in four sessions over two weeks. Data were analyzed using paired sample t-test with a significance level of α = 0.05. Results: The influence test used was a paired sample t test, with a significance level of α<0.05. The results of this study show that there is an effect of dhikr therapy on the quality of life of chronic kidney failure patients undergoing hemodialysis at Labuang Baji Hospital Makassar. Conclusion: Dhikr therapy has a significant positive effect on improving the quality of life of patients with chronic kidney disease undergoing hemodialysis. It is recommended that spiritual interventions such as dhikr be integrated into routine care for hemodialysis patients as part of holistic nursing practice.